Perspektif Konselor Indonesia terhadap Pendekatan Konseling Feminis - Arifah Wulandari; Septia Rahmawati (Universitas Sebelas Maret, 2025)
This study aims to analyze the perspective of Indonesian counselors on the feminist counseling approach. In addition, the feminist counseling approach gives importance to counseling theory, this counseling approach is an approach that is not commonly used in Indonesia. The method used in this research is a qualitative research design. Data were collected through interviews, observations, and documentation studies and analyzed using data triangulation techniques. The subjects of this study consisted of 5 school counselors at the junior high and high school levels. The results show that school counselors have limited theoretical background regarding the feminist counseling approach and are based on the concept of the feminist movement.